2016
DOI: 10.1371/journal.pntd.0004345
|View full text |Cite
|
Sign up to set email alerts
|

Pauci- and Multibacillary Leprosy: Two Distinct, Genetically Neglected Diseases

Abstract: After sustained exposure to Mycobacterium leprae, only a subset of exposed individuals develops clinical leprosy. Moreover, leprosy patients show a wide spectrum of clinical manifestations that extend from the paucibacillary (PB) to the multibacillary (MB) form of the disease. This “polarization” of leprosy has long been a major focus of investigation for immunologists because of the different immune response in these two forms. But while leprosy per se has been shown to be under tight human genetic control, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
76
1
8

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(91 citation statements)
references
References 84 publications
(93 reference statements)
6
76
1
8
Order By: Relevance
“…All the tag SNPs were in HWE in both controls and cases (Table S2). The observed distributions of allele and genotype frequencies in leprosy patients and controls were summarized in Tables 1 and S3, Recently, Gaschignard and colleagues performed association study using leprosy clinical forms as phenotypes (MB and PB) and they found that this is a powerful strategy to identify genetic factors affecting disease polarization [41]. However, we found no association of TFAM and POLG SNPs with disease polarization when we compared MB patients with PB patients (Tables 1, S3 and S4).…”
Section: Tfam Rs1049432 and Polg Rs3176238 Conferred Genetic Susceptimentioning
confidence: 81%
“…All the tag SNPs were in HWE in both controls and cases (Table S2). The observed distributions of allele and genotype frequencies in leprosy patients and controls were summarized in Tables 1 and S3, Recently, Gaschignard and colleagues performed association study using leprosy clinical forms as phenotypes (MB and PB) and they found that this is a powerful strategy to identify genetic factors affecting disease polarization [41]. However, we found no association of TFAM and POLG SNPs with disease polarization when we compared MB patients with PB patients (Tables 1, S3 and S4).…”
Section: Tfam Rs1049432 and Polg Rs3176238 Conferred Genetic Susceptimentioning
confidence: 81%
“…Leucine-rich repeat kinase 2 has also been genetically linked to Leprosy, a chronic dermato-neurological disorder caused by long-term infection with Mycobacterium leprae. Based on the clinical symptomology resulting from bacterial load and individual immune responses, leprosy acts as a spectrum of disease ranging from paucibacillary to multibacillary subtypes (Gaschignard et al, 2016). GWAS analysis of a Han Chinese cohort first suggested an association of LRRK2 rs1873613 with Leprosy per se, and in particular a significant association of LRRK2 rs1491938 with the multibacillary form of leprosy (Zhang F. R. et al, 2009).…”
Section: Lrrk2 Is Genetically Implicated In Diseasementioning
confidence: 99%
“…Despite the effectiveness of treatment, transmission likely occurs prior to diagnosis since it is primarily detected based solely on clinical findings. As yet there is no gold standard method to differentiate asymptomatic infection from disease, and early detection and unambiguous diagnosis is incredibly difficult [5][6][7][8]. As exposure to the etiological agent is not sufficient to develop the disease [9], it is assumed that early diagnosis is key in controlling the disease transmission, along with chemo-and immunoprophylactic strategies for high risk individuals, such as household contacts [10].…”
Section: Introductionmentioning
confidence: 99%